Dynamic response of an annular circular plate made of shape memory alloy using differential quadrature method. (June 2022) - Barati, Amir Hossein Nasrollah; Jafari, Ali Asghar; Haghighi, Shahram Etemadi; Maghsoudpour, Adel
This study investigates the dynamic response of an annular circular plate with clamped edges under harmonic load. The circular plate is analyzed based on the first-order shear deformation theory (FSDT). The Boyd-Lagoudas constitutive model is used to simulate the pseudoelastic behavior, and Hamilton's principle is used to obtain the equations of motion. Also, differential quadrature and Newmark methods are utilized to obtain the time and frequency responses of the plate. The phase transformation effects are studied on the time and frequency responses of the plate. Then, the accuracy of these results is checked with the available literature and ABAQUS software. Results indicate that the alloy phase transformation leads to reduced material strength and the nonlinear behavior of the alloy.